Evaluation of collagen-based membranes for guided bone regeneration, by three-dimensional computerized microtomography - Coelho, Paulo Guilherme; Giro, Gabriela [UNESP]; Kim, Wanki; Granato, Rodrigo; Marin, Charles; Bonfante, Estevam Augusto; Bonfante, Samara; Lilin, Thomas; Suzuki, Marcelo (Elsevier B.V., 2012)
Objective. The aim of this study was to evaluate the use of a collagen-based membrane compared with no treatment on guided bone regeneration by 3-dimensional computerized microtomography (mu CT).Study Design. Defects were created between the mesial and distal premolar roots of the second and third premolars (beagle dogs; n = 8). A collagen-based membrane (Vitala; Osteogenics Biomedical Inc., TX, USA) was placed in one of the defects (membrane group; n = 16), and the other was left untreated (no-membrane group; n = 16). Left and right sides provided healing samples for 2 and 16 weeks. Three-dimensional bone architecture was acquired by mu CT and categorized as fully regenerated (F, bone height and width) or nonregenerated (N).Results. Chi-square tests (95% level of significance) showed that tooth did not have an effect on outcome (P = .5). Significantly higher F outcomes were observed at 16 weeks than 2 weeks (P = .008) and in membrane group than in no-membrane group (P = .008).Conclusions. The collagen-based membrane influenced bone regeneration at the furcation. (Oral Surg Oral Med Oral Pathol Oral Radiol 2012;114:437-443)